Metabolites profiling, in-vitro and molecular docking studies of five legume seeds for Alzheimer’s disease - Rana M. Ibrahim; Passent M. Abdel-Baki; Osama G. Mohamed; Ahmed A. Al-Karmalawy; Ashootosh Tripathi; Riham A. El-Shiekh (Scientific Reports, 2024)
Abstract Even though legumes are valuable medicinal plants with edible seeds that are extensively consumed worldwide, there is little information available on the metabolic variations between different dietary beans and their influence as potential anti-cholinesterase agents. High-resolution liquid chromatography coupled with mass spectrometry in positive and negative ionization modes combined with multivariate analysis were used to explore differences in the metabolic profiles of five commonly edible seeds, fava bean, black-eyed pea, kidney bean, red lentil, and chickpea. A total of 139 metabolites from various classes were identified including saponins, alkaloids, phenolic acids, iridoids, and terpenes. Chickpea showed the highest antioxidant and anti-cholinesterase effects, followed by kidney beans. Supervised and unsupervised chemometric analysis determined that species could be distinguished by their different discriminatory metabolites. The major metabolic pathways in legumes were also studied. Glycerophospholipid metabolism was the most significantly enriched KEGG pathway. Pearson’s correlation analysis pinpointed 18 metabolites that were positively correlated with the anti-cholinesterase activity. Molecular docking of the biomarkers to the active sites of acetyl- and butyryl-cholinesterase enzymes revealed promising binding scores, validating the correlation results. The present study will add to the metabolomic analysis of legumes and their nutritional value and advocate their inclusion in anti-Alzheimer’s formulations.